Critical dictionary of film and television theory - Pearson, Roberta E.; Simpson, Philip (Routledge, 2001)
This new dictionary is the first in-depth reference to cover the approaches deployed in the study of the moving image as well as defining key theoretical terms. Featuring over 400 entries ranging from 500 to 3,000 words, this resource gives a context to the debates surrounding the terms rather than simplistic "definitions." The dictionary is destined to be a key reference for students of communication, media, film and cultural studies, art, design and literature